Translation Strategies for a Novel Constructed as a Language Textbook: Djinn, un Trou Rouge Entre les Paves Disjoints - Guzelyurek Celik, Pinar; Arslan Ozcan, Lale (HACETTEPE UNIV, 2016)
The novel Djinn, Un trou rouge entre les paves disjoints by Alain Robbe-Grillet, was written first of all as a grammar textbook to be used in French language courses at school. Therefore, Djinn has two structures that complement each other, just like two sides of a coin: a novel and a grammar textbook, in other words, it is both a literary work and a grammar textbook at the same time. Another interesting aspect of the work is the fact that it contains different styles of narration while teaching the grammar rules of French. This paper aims to present what the challenges are for the translator during the translation process of this novel into Turkish which was written to teach the readership whose mother tongue is English, the grammar rules of the French language by retaining all its characteristics, and what solutions he or she can provide to overcome such challenges. Different translation attitudes that can be followed for the translation of Djinn by retaining the style as a novel constructed by Robbe-Grillet into Turkish and strategies and suggestions will constitute the fmal part of this paper.
Keywords: grammar textbook; translation; novel; Djinn; translation strategies; Education & Educational Research